The diagnostics of a state of an aesthetic development of the elementary' school pupils during the choreographic activity (Pedagogy of Higher and Secondary Education, 2006)
The article represents the results of diagnostics of the levels of an aesthetic development of pupils ofprimary classes huy resources of choreography.
Keywords: elementary school; aesthetic education; choreography; pedagogical diagnostics